Analisis Kesalahan Siswa dalam Menyelesaikan Soal Bilangan Berpangkat dan Bentuk Akar - Bota, Mariana Ra; Lede, Yulius Keremata; Making, Samuel R.M.; Patty, Elyakim N.S.; Iriyani, Sri Astuti (CT. Rajawali media Utama, 2024)
This study aims to describe students' errors in solving class X problems of power numbers and root forms and analyze the factors that cause students to make mistakes. This type of research is descriptive qualitative. The research subjects were class X students of SMK Kasimo in the 2023/2024 academic year. The data collection methods used in this research are tests, interviews, and documentation. Data analysis techniques through data reduction, data presentation, and conclusion drawing. The results showed that the errors made by students in solving problems of power numbers and root forms: (1) errors in understanding the meaning of the problem; (2) errors in understanding and applying concepts; and (3) errors in calculating. The factors that cause students to make mistakes are students do not understand the meaning of the question asked, students have not mastered the prerequisite material such as: exponent numbers, students do not understand the material, students forget the formula, students lack practice in solving problems about power numbers and root forms, students are less careful in calculating, students do not check the answers that have been done.